2002
DOI: 10.1007/s004640080069
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity a high-risk factor for laparoscopic colorectal surgery?

Abstract: Laparoscopic colorectal segmental resections are feasible in obese patients. However, increased rates of conversion to laparotomy should be anticipated and the risk of postoperative complications is significantly increased, prolonging the length of hospitalization when compared to that of nonobese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
215
9
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(242 citation statements)
references
References 20 publications
11
215
9
3
Order By: Relevance
“…These technical limitations in the right colon resection of obese patients increase the likelihood of converting an EA technique to a fully open resection. Thus, a totally laparoscopic IA technique may be desirable in obese patients as it may help avoid larger incisions and higher complication rates compared to that of a laparoscopic-assisted EA technique [23]. Additionally, the benefits of smaller incisions achieved by an IA technique decreasing the risk of postoperative pain and incisional hernias have been well established [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These technical limitations in the right colon resection of obese patients increase the likelihood of converting an EA technique to a fully open resection. Thus, a totally laparoscopic IA technique may be desirable in obese patients as it may help avoid larger incisions and higher complication rates compared to that of a laparoscopic-assisted EA technique [23]. Additionally, the benefits of smaller incisions achieved by an IA technique decreasing the risk of postoperative pain and incisional hernias have been well established [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons have generally thought that obesity might possibly increase the incidences of intraoperative and/ or postoperative anesthetic complications [14], intraoperative bleeding, and surgical complications, and it is also thought that obesity may increase operation times and the risk of cardiopulmonary diseases [9,10]. Some studies have reported the effect of obesity on open gastric cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons have long thought that obesity might increase the rate of intraoperative or postoperative complications [9,10]. A recent report from Japan concluded that a higher BMI hampered the performance of lymphadenectomy during gastric cancer surgery, and a higher BMI was reported as an independent predictor of cancer recurrence [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have demonstrated that obesity is associated with high conversion rates [16][17][18]. One of the difficulties of performing laparoscopic surgery on obese patients is obtaining good visualization of the surgical field.…”
Section: Discussionmentioning
confidence: 99%